Celebrating Christmas in Bay Area - Watkins, Howard::::::::: (1981)
Jean and Don's home in Burlingame; Front: Kit Sanders, Betty Sanders, Adam Watkins, Harry Dalva, his niece Heidi; Middle: Shirley Griffenhagen, Frances Kamp, Leslie Prusia, Jean, Danny Duncan, Christine Watkins, Bill Sanders; Back: ??Peggy Sanders, Maril Turpin, Don